Methylation of DACT2 accelerates esophageal cancer development by activating Wnt signaling - Zhang, Meiying (Oncotarget, 2016)
Esophageal cancer is one of the most common malignancies worldwide. DACT2 is frequently methylated in human lung, hepatic, gastric and thyroid cancers. The methylation status and function of DACT2 remain to be elucidated in human esophageal cancer. Ten esophageal cancer cell lines, 42 cases of dysplasia and 126 cases of primary esophageal cancer samples were analyzed in this study. The expression of DACT2 was detected in YES2 cells, while reduced DACT2 expression levels were found in TE8 and KYSE70 cells, and complete loss of DACT2 expression was found in KYSE30, KYSE140, KYSE150, KYSE410, KYSE450, TE3 and TE7 cells. Loss of expression or reduced expression of DACT2 correlated with promoter region hypermethylation in esophageal cancer cells. Restoration of DACT2 expression was induced by 5-aza-2′-deoxycytidine. In human primary esophageal squamous carcinoma, 69% (87/126) of samples were methylated. Methylation of DACT2 was significantly associated with tumor stage and metastasis (P < 0.01, P < 0.05). DACT2 suppressed colony formation, cell migration and invasion in esophageal cancer cells, and it also suppressed esophageal cancer cell xenograft growth. DACT2 inhibited Wnt signaling in human esophageal cancer cells. In conclusion, DACT2 is frequently methylated in human esophageal cancer and its expression is regulated by promoter region methylation. DACT2 suppresses esophageal cancer growth by inhibiting Wnt signaling.